Case Report: Identification Pathogenic Abnormal Splicing of BBS1 Causing Bardet–Biedl Syndrome Type I (BBS1) due to Missense Mutation - Yan, Kai; Sun, Yixi; Yang, Yanmei; Liu, Bei; Dong, Minyue (Frontiers in Genetics, 2022)
Conventionally, protein features affected by missense mutation were attribute to destroy important domain with amino acid alternation and it was difficult to clearly specify the pathogenicity of a novel missense mutation. Nevertheless, the associations between missense mutations and abnormal splicing are nowadays increasingly reported. Rarely, some missense mutations, locating at the non-canonical splicing sites, are observed to damage the splicing process. In this study, a couple has three adverse pregnancy history that the affected fetus presented typical polydactyly, renal abnormalities and cerebral ventriculomegaly. To identify its genetic etiology, whole-exome sequencing was performed and the missense mutation c.1339G>A was identified, which was located at the non-canonical splicing sites of the BBS1 gene. Then, reverse transcription polymerase chain reaction was carried out and demonstrated extra 115bp originating from Intron 13 cut into cDNA which generated a predicted premature termination codon (PTC) in the BBS1 protein. Further expression analysis by using Real-time reverse-transcribed PCR confirmed the occurrence of nonsense-mediated decay (NMD). Therefore, the pathogenicity of the missense mutation c.1339G>A was explicit and our study helped to extend the spectrum of pathogenic mutations in Bardet-Biedl syndrome type I.